Peranan Badan Usaha Milik Desa Sebagai Upaya Meningkatkan Pendapatan Asli Desa (Studi Kasus Bumdes Bumi Raharjo Kecamatan Bumi Ratu Nuban Lampung Tengah - Amelia, Aninda; Yateno, Yateno (Universitas Muhammadiyah Metro, 2021)
ABSTRACT This research was used to determine the role of Village Owned Enterprises as an effort to increase village original income at Bumi Raharjo Village Owned Enterprises, Bumi Ratu Nuban District, Central Lampung. Village owned enterprises (BUMDES) are village business institutions managed by the community and village government in an effort to strengthen the village economy and are formed based on the needs and potential of the village. BUMDES is a pillar of economic activity in the village that functions as a social institution (social institution) and commercial (commercial institution). The type of research used is quantitative research with a comparative research approach with paired sample t-test which aims to determine the role of Village Owned Enterprises in efforts to increase village original income before and after the existence of BUMDES. After conducting the research, it shows that Village Owned Enterprises as an effort to increase village original income at Bumi Raharjo Village Owned Enterprises, Bumi Ratu Nuban District, Central Lampung, play a role in efforts to increase village original income. One new approach that is expected to be able to stimulate and move the economy in rural areas is through the establishment of Village Owned Enterprises (BUMDES) which are fully managed by village communities. This economic institution must be based on the desire of the village community, which departs from the potential that is managed properly in order to increase Village Original Income (PADES). Keywords: Village Owned Enterprises (BUMDES), Role of BUMDES, Efforts to Increase Village Original Income (PADES).